2017
DOI: 10.1177/1078390316685154
|View full text |Cite
|
Sign up to set email alerts
|

National Organization of Nurse Practitioner Faculties

Abstract: Significant challenges exist to growing the PMH NP lifespan workforce including how to assist PMH clinical nurse specialists, Adult PMH NPs, and other NPs wanting to obtain the PMH NP lifespan degree.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 13 publications
0
5
0
Order By: Relevance
“…Of equal concern is the small proportion of respondents (11%) who indicated that the majority of their patients were over 60 years of age. This need to develop a workforce for both ends of the age spectrum has been articulated in the literature (Delaney, 2015; Stephens, Harris, & Buron, 2015), but at this point there are few reports of how PMH APRN educational programs are adapting curriculum to this need (Vanderhoef & Delaney, 2017). It will be important to monitor how PMH NP education programs integrate training for these age-related populations.…”
Section: Discussionmentioning
confidence: 99%
“…Of equal concern is the small proportion of respondents (11%) who indicated that the majority of their patients were over 60 years of age. This need to develop a workforce for both ends of the age spectrum has been articulated in the literature (Delaney, 2015; Stephens, Harris, & Buron, 2015), but at this point there are few reports of how PMH APRN educational programs are adapting curriculum to this need (Vanderhoef & Delaney, 2017). It will be important to monitor how PMH NP education programs integrate training for these age-related populations.…”
Section: Discussionmentioning
confidence: 99%
“…Many residents did not perceive leadership as an essential part of the NP role, yet NP education often emphasizes leadership as part of NP competencies. 22 From our findings, it is possible that residents' lack of experience with NPs as leaders helps maintain the prototype of the physician leader and likely also explains why the majority of residents assumed that the resuscitation leader in the video was a physician.…”
Section: Discussionmentioning
confidence: 83%
“…However, a recent survey of graduate programs indicates that programs are struggling to obtain child clinical practicum hours. In this same survey, data point to significant differences in how programs are approaching the core content, particularly around the psychotherapeutic role (Vanderhoef & Delaney, 2017). In addition, given the increasing presence of integrated care, there is a need to develop more consistent approaches to the medical factors in presentations, complications, and comorbidities that graduates will encounter in clinical practice.…”
Section: Discussionmentioning
confidence: 99%